Penerapan Manajemen Operasional dalam Peningkatan Sumber Daya Manusia pada Perusahaan - Marichicha Puicha L. Sianturi (Jurnal Publikasi Ilmu Manajemen, 2024)
A company is a place where production activities occur and where all factors of production, both goods and services, gather. A manufacturing company is a business or industry that is constantly moving, has high economic value and can be used directly by consumers. Every worker or employee in a business entity or company has their own duties and functions that have been determined or agreed upon before starting work. The method used in this research activity uses a qualitative approach where this approach explores and understands the meaning of some individuals or groups of people originating from social problems (Creswell & Poth, 2018) whereas according to Schindler & Cooper (2013) Qualitative research is designed to tell researchers how (process) and why (meaning) something happens as it does. Application in improving the workforce, such as: 1. Human Resources 2. Human Resources Development 3. Objectives of Human Resources Development and Benefits in increasing the workforce, such as: 1. Increasing Work Morale 2. Increasing Performance 3. Supporting Productivity 4. Building Company Image Suggestions for further research, the addition of several categories for the company’s development and productivity of required human resources.